The Fulfilled of Love and Belonging Needs in Elizabeth as the Main Character of Pride and Prejudice Novel: Psychological Approach - Diffyanie; Zia Hisni Mubarak (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study explores the fulfilment of love and belonging needs in Elizabeth Bennet, the central character of Jane Austen's Pride and Prejudice, using a psychological approach based on Abraham Maslow's Hierarchy of Needs. The research examines how Elizabeth navigates relationships, personal growth, and societal expectations to achieve emotional fulfilment. By analysing her interactions with family members, friends, and Mr. Darcy, the study highlights the challenges and resolutions that shape Elizabeth's journey. Misunderstandings, prejudices, and class differences initially hinder Elizabeth’s ability to feel love and belonging, but through mutual respect and emotional growth, these needs are ultimately fulfilled. This qualitative research uses descriptive analysis and intrinsic-extrinsic techniques to reveal the causes and effects of Elizabeth's emotional journey, emphasizing the importance of trust, mutual understanding, and personal growth in fulfilling psychological needs. The findings underscore the complexities of relationships and personal development in achieving love and belonging, offering insights into human behaviour and motivation as reflected in literature.